Analisis Motivasi dan Hasil Belajar IPAS Siswa pada Materi Bagaimana Aku Tumbuh Besar - Rizky Indah Palupi; Supriyanto; Viktor Pandra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the relationship between learning motivation and IPAS learning outcomes on the topic How I Grow Up among fifth-grade students of SD Negeri 61 Lubuklinggau. The method used was a descriptive quantitative approach involving 28 students as research subjects. The research instruments consisted of 15 multiple-choice questions to measure learning outcomes and 22 Likert-scale questionnaire items to assess students’ learning motivation. The results showed that the average learning motivation reached 71.3%, categorized as moderate, while the average IPAS learning outcomes reached 76.6%, also categorized as moderate. The analysis indicated a positive relationship between learning motivation and IPAS learning outcomes, although the strength of the relationship was classified as moderate. In conclusion, learning motivation plays a role in students’ IPAS learning outcomes, and improving learning motivation may contribute to better academic achievement. Keywords: Learning Outcomes, IPAS, Learning Motivation